2016
DOI: 10.1038/srep23204
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72 ablation causes immune dysregulation characterized by leukocyte expansion, autoantibody production and glomerulonephropathy in mice

Abstract: The expansion of a hexanucleotide (GGGGCC) repeat in C9ORF72 is the most common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Both the function of C9ORF72 and the mechanism by which the repeat expansion drives neuropathology are unknown. To examine whether C9ORF72 haploinsufficiency induces neurological disease, we created a C9orf72-deficient mouse line. Null mice developed a robust immune phenotype characterized by myeloid expansion, T cell activation, and increased plasma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
227
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(257 citation statements)
references
References 66 publications
(75 reference statements)
23
227
3
Order By: Relevance
“…Transplantation of mutant (−/−) bone marrow cells to wild type (WT) animals caused autoimmunity and premature mortality, whereas transplantation of WT mice bone marrow cells into mutant (−/−) animals improved phenotype (2). This work is in agreement with the work of Atanasio et al (5) who found that C9orf72 null mice developed myeloid expansion, T cell activation and increased plasma cells. C9orf72 null mice had autoantibodies and glomerulopathy, abnormalities reminiscent of SLE.…”
supporting
confidence: 82%
“…Transplantation of mutant (−/−) bone marrow cells to wild type (WT) animals caused autoimmunity and premature mortality, whereas transplantation of WT mice bone marrow cells into mutant (−/−) animals improved phenotype (2). This work is in agreement with the work of Atanasio et al (5) who found that C9orf72 null mice developed myeloid expansion, T cell activation and increased plasma cells. C9orf72 null mice had autoantibodies and glomerulopathy, abnormalities reminiscent of SLE.…”
supporting
confidence: 82%
“…Several studies of germline knockout of C9orf72 in mice were published last year that provide insights into how haploinsufficiency of C9orf72 could contribute to neurodegeneration (105)(106)(107). None of the mice in these studies showed neurodegeneration or motor system dysfunction consistent with ALS/FTD phenotypes, suggesting that C9orf72 function is not as critical in mammalian neurons as was observed in lower organisms.…”
Section: C9orf72 Myeloid Cells and Immunity: An Unexpected Connectionmentioning
confidence: 99%
“…Moreover, increased activated circulating macrophages, abnormal numbers of CD4 T‐cells, antibodies and circulating immune complex have been described in blood of ALS patients, but the results have been inconsistent 70, 71. Interestingly, the development of C9orf72 null mouse models, after identification of a mutated version of this gene in a significant proportion of ALS patients, did not lead to overt motor impairment 72, 73. Instead, an array of peripheral immune organ abnormalities arose, including splenomegaly, lymphadenopathy and eventually an autoimmune‐like phenotype 72, 73.…”
Section: Status Of Neuroinflammation In Als and Smamentioning
confidence: 99%
“…Interestingly, the development of C9orf72 null mouse models, after identification of a mutated version of this gene in a significant proportion of ALS patients, did not lead to overt motor impairment 72, 73. Instead, an array of peripheral immune organ abnormalities arose, including splenomegaly, lymphadenopathy and eventually an autoimmune‐like phenotype 72, 73. Nonetheless, macrophages and microglia appeared particularly susceptible, showing lysosomal dysfunction and a proinflammatory state 73.…”
Section: Status Of Neuroinflammation In Als and Smamentioning
confidence: 99%